2017
DOI: 10.1080/16000870.2017.1299910
|View full text |Cite
|
Sign up to set email alerts
|

The effect of model bias on Atlantic freshwater transport and implications for AMOC bi-stability

Abstract: Evidence from paleo-proxy records suggests that the Atlantic Meridional Overturning Circulation (AMOC) can be in both an AMOC on state, the AMOC as we observe it today, and an AMOC off state, where the AMOC becomes extremely weak or even collapses. The freshwater transport due to the AMOC (M ov ) at 34°S in the Atlantic has often been used as an indicator for bi-stability, with a positive M ov suggesting a monostable AMOC and a negative M ov suggesting a bi-stable AMOC. Often studies have shown that the sign o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
106
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 52 publications
14
106
5
Order By: Relevance
“…These F gyre transports exhibit a marked antisymmetric pattern around the mean ITCZ location at~5°N, redistributing freshwater within a 0-300 m upper ocean layer in the subtropics of both hemispheres. However, applying the same reasoning as for F ov at 34°S (see section 1), one would conclude that all models are therefore unstable, as they systematically simulate a large negative F ov in the NASG (see Figure 1b and Mecking et al, 2017). Changes in evaporation minus precipitation induced by an AMOC collapse, such as an ITCZ shift, also support the large F gyre changes found by Mecking et al (2016) in the South Atlantic.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These F gyre transports exhibit a marked antisymmetric pattern around the mean ITCZ location at~5°N, redistributing freshwater within a 0-300 m upper ocean layer in the subtropics of both hemispheres. However, applying the same reasoning as for F ov at 34°S (see section 1), one would conclude that all models are therefore unstable, as they systematically simulate a large negative F ov in the NASG (see Figure 1b and Mecking et al, 2017). Changes in evaporation minus precipitation induced by an AMOC collapse, such as an ITCZ shift, also support the large F gyre changes found by Mecking et al (2016) in the South Atlantic.…”
Section: Discussionmentioning
confidence: 71%
“…At 34°S, F gyre is consistently larger than F ov , so that the total transport is actually northward and compensates for the net evaporation in the subtropical South Atlantic. Yin and Stouffer (2007) and Mecking et al (2016) instead suggest that a better bistability indicator might be to measure F ov across the NASG where the salinity bias-corrected CMIP5 models show the largest correlations between F ov and AMOC strength (Mecking et al, 2017). In a freshwater hosing experiment with an eddy-permitting coupled model, Mecking et al (2016) showed that the dominant response of F gyre at 34°S is over twice as large as the changes in F ov , despite the total AMOC collapsed.…”
Section: Discussionmentioning
confidence: 99%
“…There may be several reasons for this diversity in model behavior. First, several studies suggest that the current generation of CGCMs may suffer from biases that hinder the models' ability to show AMOC multiple equilibria (Hawkins et al, ; Huisman et al, ; Liu et al, , ; Mecking et al, ; Weaver et al, ). Several of these studies point out that GCMs often have a fresh bias in the South Atlantic that affects the amplitude, if not the sign, of F ovS and hence the stability regime in which the modeled AMOC resides.…”
Section: Multiple Equilibria Of Amoc In a Hierarchy Of Modelsmentioning
confidence: 99%
“…If, instead, the AMOC exports freshwater ( F ovS <0), haline forcing would oppose the circulation, and a reverse SA circulation would exist as an alternative equilibrium. Studies with GCMs found the condition F ovS =0 to be a remarkably accurate indicator of the boundary between the monostable and bistable regimes (Cimatoribus et al, ; De Vries & Weber, ; Drijfhout et al, ; Hawkins et al, ; Jackson, ; Mecking et al, ; Weber & Drijfhout, ). In fact, several studies with comprehensive GCMs showed that the stability characteristics of the AMOC can be altered by constraining F ovS to be positive or negative, as predicted by box models (Cimatoribus et al, ; De Vries & Weber, ; Jackson, ; Liu et al, ).…”
Section: Feedbacks Controlling Amoc Stabilitymentioning
confidence: 99%
See 1 more Smart Citation